Aluminum‐Based Plasmonic Photocatalysis. (25th January 2017) - Chen, Yan; Xin, Xin; Zhang, Nan; Xu, Yi‐Jun
Abstract : Studies on localized surface plasmon resonance (LSPR) of noble metals (mainly gold and silver) regarding solar‐driven photocatalysis have been attracting enormous interests over the past two decades. As research on LSPR continues to expand, recently, aluminum (Al) with respect to plasmonic enhanced photocatalysis beyond such noble metals has attracted considerable attention. Al as an abundant and relatively inexpensive metal holds great promise for plasmonic photocatalysis with outstanding light‐harvesting capacity and performance in virtue of its unique optical characteristics. Herein, a short review is given on the related basics of LSPR, and the key factors including the size, shape, and oxide formation of Al nanostructures, which significantly influence the optical response of Al. In particular, photocatalytic applications in artificial photoredox processes with regard to plasmonic Al are outlined. In addition, some perspectives on the opportunity and challenge for future development of this research field are offered. Abstract : Aluminum (Al) unfolds outstanding light‐harvesting capacity and performance in virtue of its unique optical characteristics, which are enabled by a localized surface plasmon resonance (LSPR) effect. Based on these properties, Al as a cost‐efficient emerging material opens up an avenue with the significant utilization of solar energy toward plasmon‐enhanced photocatalysis.